PERAN CORPORATE GOVERNANCE TERHADAP PENERAPAN ENTERPRISE RISK MANAGEMENT: STUDI PERBANDINGAN BANK INDONESIA DAN BANK MALAYSIA - Karina Aulia Putri; Rita Anugerah; Novita Indrawati (PEKBIS, 2020)
Corporate governance is a system, process, set of rules that regulate relationshipsbetween various interested parties in order to achieve an organizational goal.Therefore, corporate governance is expected to improve the implementation ofenterprise risk management.This study has several objectives: first, to examine therole of corporate governance in implementing ERM at Indonesia’s Bank. Second, toexamine the role of corporate governance in implementing ERM at Malaysia’s Bank.Third, to see the difference in the implementation of ERM influenced by corporategovernance in the two countries (Indonesia and Malaysia). Data is obtained from theannual reports of companies listed on the IDX and KLSE for the period of 2016-2017. Using SPSS 21 the results of this study show that corporate governance(independent commissioners, audit committee meetings, risk monitoring committeefunds, and competencies of these committees) has an influence on theimplementation of ERM in Indonesia. While, Malaysia, only independentcommissioners and risk monitoring committee’s meetings influence theimplementation of ERM. The results of this study confirm that the implementation ofERM in both countries (Indonesia and Malaysia) is different, because the practice ofcorporate governance between the two countries is also different.